Exposure to endotoxin level in inhalable rice dust among rice mill workers - Zin, Ros Aida Mohd (Universiti Sains Malaysia, 2016)
Endotoxins are the lipid portions of lipopolysaccharides (LPSs) which is a part of the outer membrane of the cell wall of gram-negative bacteria. Rice dust containing endotoxin can cause systemic inflammatory response syndrome (SIRS) and multiple organ dysfunction syndromes (MODS). The aim and objective of this study are to compare the concentration of dust, endotoxin exposure level and lung function between rice mill workers and management workers in Kelantan. Samples were collected using Institute of Occupational Medicine (IOM) inhalable dust sampler loaded with glass fiber filter (GFA) for 8 hours and analysed by using Limulus amebocyte lysate (LAL) test. The lung functions were tested by using the spirometer to measure the amount of maximal air breathed out over pre-exposure (before work) and post-exposure (after work). Results showed that the dust concentration (mg/m3) of rice mill workers (median: 8.86, range: 2.68-15.93) was significantly different compared with the LJSM management workers (median: 1.47, range: 0.22-2.53) and the rice mill management workers (median: 0.70, range: 0.47-1.72) p=0.005. The endotoxin concentration (EU/ml) of the rice mill workers (median: 0.14, range: 0.11- 0.16) was significantly different compared with the rice mill management workers (median: 0.06, range: 0.03-0.10) and the USM management workers (median: 0.05, range: 0.04- 0.09). The forced vital capacity (FVC), forced expiratory volume in one second (FEV1) and FEV1/FVC% among the three groups shows no different between pre and post-exposure at (p-0.601, p-0.960 and p=0.660), respectively. This study is important to promote health awareness among workers involving knowledge, attitude and safety practices about personal protective equipment (PPE) and gives benefit for other researchers for further investigations about rice dust in Malaysia.